Advances in the development of tunable lenses in Mexico - Santiago-Alvarado, Agustin; Vazquez-Montiel, Sergio; Gonzalez-Garcia, Jorge; Iturbide-Jimenez, Fernando; Cruz-Felix, Angel S.; Cruz-Martinez, Victor; Lopez-Lopez, Enrique A.; Castro-Gonzalez, Graciela (Photonics Letters of Poland, 2015)
Advances in the development of tunable lenses have produced more compact, simple and lightweight optical systems. There are different types of tunable lenses; among the simplest we can find liquid and solid lenses, which only require a mechanical mount to change the shape of the lenses. We present the analysis and results that were obtained recently from these two types of lenses which have produced an improvement in the quality of images formation as well as some of their future applications. Full Text: PDF References N. Nguyen, "Micro-optofluidic Lenses: A review", Biomicrofluidics 4, 031501-1 (2010). CrossRef U. Levy, R. Shamai, "Tunable optofluidic devices", Microfluidics and Nanofluidics 4, 97 (2008). CrossRef G. R. Xiong et al. "Liquid microlens with tunable focal length and light transmission", Appl. Phys. Lett. 92, 241119 (2008). CrossRef A. Weber and H. Zappe, IEEE/ASME JMEMS 17, 1218 (2008). A. Santiago-Alvarado et al. "Simulating the functioning of variable focus length liquid-filled lenses using the finite element method (FEM)", Optik, 124, 1003 (2013). CrossRef B. Malouin et al. "Electromagnetic liquid pistons for capillarity-based pumping", Lab. Chip 11, 393 (2011). CrossRef W. Wang and J. Fang, "Design, fabrication and testing of a micromachined integrated tunable microlens", J. Micromech. Microeng 16, 1221 (2006). CrossRef C. López, C. Lee and A. Hirsa, "Electrochemically activated adaptive liquid lens", Appl. Phys. Lett. 87, 134102 (2005). CrossRef N. Nam-Trung, "Micro-optofluidic Lenses: A review", BIOMICROFLUIDICS 4,031501 (2010). CrossRef I. Jung et al. "Dynamically tunable hemispherical electronic eye camera system with adjustable zoom capability", Proc. Natl. Acad. Sci. 108, 1788 (2011). CrossRef A. Cruz-Félix, A. Santiago-Alvarado, IJESIT 3, 563 (2014). R. Kingslake, Lens Design Fundamental, (New York, Academic Press 1978). A. Santiago Alvarado et al. Jour. of Phys: Conf. Series 274 (2011). A. Santiago Alvarado et al. "Measurement of aberrations of a solid elastic lens using a point-diffraction interferometer", Opt. Eng. 49, 123401 (2010). CrossRef